Peak Flow Meter Equipped with Inspection Results Indicator - Nadiya Garnis Sallyfan; Endro Yulianto; Torib Hamzah (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Peak Flow Meter (PFM) is a tool to measure the Peak Flow of Air Expiration in the road (PFR) or commonly referred to as Peak Expiration Flow (PEF) and to connect asthma. The value of PEF can help a number of factors in age, respiratory muscle strength, height and gender. Airway measurements are used to measure patients suffering from asthma. This peak flow meter tool works based on the air pressure produced from the patient's puff using the MPX5100GP pressure sensor in the range of 0 to 100 kPa and the voltage output is 0.2 to 4.7 VDC to increase wind pressure in the patient. From the pressure converted to voltage and enter the 0 from the Arduino nano minimum system circuit to be processed into analog data and then put into units of liters / second, the value of the flow meter is sent and replaced to a PC with the Delphi7 application. The measurement results of PEF values at peak flow meters have an error value of less than 5% This peak flow meter tool also has a consideration value of 0.095475 so that this tool can be said to be very certain to be used as asthma. Then it can be concluded that the peak flow meter is feasible and meets the specified requirements